Analisis Unsur-Unsur Tasybih Pada Mahall al-Qiyam Dalam Kitab Al-Barzanji Karya Syekh Ja’far Al-Barzanji - Siti Nurhalisa (Jurnal Pendidikan Bahasa Arab, 2024)
The book Al-Barzanji is a literary work that narrates the life of Prophet Muhammad (peace be upon him) from before his birth to his passing. The work begins with praise from the author towards Prophet Muhammad (peace be upon him), as recorded at the outset with the word "Athir". Here, "Athir" describes a situation or place that honors the presence of Prophet Muhammad (peace be upon him) among the community. Some also refer to it as "Marhabanan", which means a welcome to the presence of our Prophet. This research focuses on the elements of simile found within the "Mahall al-Qiyam" (place of praise) in the book Al-Barzanji. The method used by researchers to collect data in this study is documentation and recording, as described by Suharsini Arikunto. This method involves gathering data from various sources such as records, texts, books, newspapers, magazines, inscriptions, meeting notes, schedules, and others. Among the twenty-four verses in the text "Mahall al-Qiyam", there are thirteen simile elements and various forms of similes as described in the text by Syekh Ja'far Al-Barzanji. These simile elements are found in verses 6, 7, 8, 11, 12, 15, 16, 18, 19, 21, 22, 23, and 24. Here are the details of the simile elements and forms of similes in the text "Mahall al-Qiyam" according to the book Al-Barzanji: Simile elements: 13 Objects likened: 19 Simile instruments: 3 Faces of simile: 3 Forms of similes in the text "Mahall al-Qiyam" are as follows: Indrawi simile: 2 in verses 6 and 8 Compound simile: 8 in verses 7, 15, 16, 18, 19, 21, 22, and 23 Representative simile: 2 in verses 11 and 12 General simile: 1 in verse 24.